Advances in the Application of New Ultrasound Technology for the Diagnosis and Treatment of Lymphoma - Bao Rui, Chen Lu, Luo Yukun, Zhang Mingbo (Advanced Ultrasound in Diagnosis and Therapy)
Lymphoma is a common hematological malignancy with markedly increasing incidence. Its pathological types are complex and heterogeneous, and there are significant differences in treatment options and efficacy. Therefore, early and precise diagnosis, assessment of efficacy, and judgment of prognosis are key clinical problems. Ultrasound (US) has important clinical value in the diagnosis and treatment of lymphoma. This article reviews the progress made with new US technologies in improving the accuracy of diagnosis and staging of lymphoma, predicting the course of lymphoma, monitoring the progression of lesions during treatment, and assisting clinics in formulating accurate and effective treatment plans. In addition, we review the biological basis of US prediction of lymphoma and provide an outlook for future research directions.